Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/bcr-2017-223899
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular mural thrombus despite treatment with dabigatran and clopidogrel

Abstract: We describe a case with severe heart failure and moderate aortic stenosis. Due to previous atrial fibrillation and ischaemic heart disease, this patient was treated with both dabigatran and clopidogrel. Despite this, a large mural thrombus was found on echocardiography. The treatment was altered to warfarin, but the thrombus did not resolve during the next eight months.Guidelines for the use of anticoagulant treatment in left ventricular thrombus are needed. Previously, a few cases presenting resistance to nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Until recently, data have been limited to single-arm studies and case reports. [10][11][12][13][14] RED VELVT was a multicenter retrospective study that compared DOACs with warfarin and found a significant association between DOACs and SSE. 17 This contrasts with our results and 2 recently published observational studies, which showed similar to lower risk for stroke in patients treated with a DOAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, data have been limited to single-arm studies and case reports. [10][11][12][13][14] RED VELVT was a multicenter retrospective study that compared DOACs with warfarin and found a significant association between DOACs and SSE. 17 This contrasts with our results and 2 recently published observational studies, which showed similar to lower risk for stroke in patients treated with a DOAC.…”
Section: Discussionmentioning
confidence: 99%
“…Factors contributing to this interest likely include the need for continuous monitoring with warfarin, potential for reduced bleeding risk with DOACs, 8 and pharmacoeconomic studies demonstrating superior cost-effectiveness of DOACs over warfarin. 9 Although convenient, DOACs require further investigation in treating LV thrombus because the literature is limited to case reports and observational studies, [10][11][12][13][14][15][16][17] and their effectiveness remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…One hypothesis postulated is that dabigatran binds thrombin in a one-to-one molecular ratio, while one factor Xa leads to the generation of 1000 thrombin molecules, making factor Xa inhibition more attractive. Few cases of LV thrombi on dabigatran therapy have emerged in the literature [ 50 , 51 ]. The use of dabigatran for anticoagulation in mechanical heart valves was also unsuccessful in a RE-ALIGN study.…”
Section: Doacs In LV Thrombus—the Clinical Experiencementioning
confidence: 99%